Hematological alterations in fish exposed at agricultural fair - Durigon E.G.* (2019)
© 2018, Springer-Verlag London Ltd., part of Springer Nature.The objective of this study was to evaluate if there were alterations in hematological variables of fish after transportation and exhibition at an agricultural fair. We first collected blood samples from 12 fish of the species Prochilodus lineatus (curimbatá) at the Goio-En research institute; then, these animals were transported (60 km) to the agricultural fair, where they stayed for 3 days in glass aquariums exposed to the visitors of the event. On the return of the fish to the institute, we collected blood again. We performed hematological analyses, measuring hematocrit, hemoglobin concentration, and total erythrocyte count in the harvested material. We also determined mean corpuscular volume, mean corpuscular hemoglobin, and mean corpuscular hemoglobin concentration. Total leukocyte counts and leukocyte differential performed on blood smears. There were no differences in hematocrit, hemoglobin, mean corpuscular hemoglobin, leukocyte, lymphocyte, neutrophil, and monocyte concentration (P > 0.05) before and after the fair. However, the number of erythrocytes and thrombocytes were lower after the fish show (P < 0.05). Mean values of mean corpuscular volume and mean corpuscular hemoglobin was higher after the fair (P < 0.05). Stress at the fair may have reduced the number of erythrocytes and thrombotic agents, as a result of which there may have been a compensatory effect in the fish that increased the mean corpuscular volume and mean corpuscular hemoglobin concentrations, in order to maintain the transport of oxygen in the cells and homeostasis. Based on these lines of evidence, it appears that exhibition of curimbatá in fairs caused alterations in the hematological parameters, damaging homeostasis and metabolism, thus negatively affecting their development.